Angio-seal used as a bailout for incomplete hemostasis after dual perclose ProGlide deployment in transcatheter aortic valve implantation - Çakal, Beytullah; Çakal, Sinem; Karaca, Oğuz; Kızılırmak Yılmaz, Filiz; Güneş, Hacı Murat; Yıldırım, Arzu; Özcan, Özgür Ulaş; Güler, Yeliz; Boztosun, Bilal (Texas Heart Institute, 2022)
Background: The failure rate of vascular closure devices remains a significant cause of major vascular complications in contemporary transcatheter aortic valve implantation practice. Methods: This research aimed to evaluate use of the Angio-Seal device in a bailout context in the setting of incomplete hemostasis following use of dual Perclose ProGlide devices in patients undergoing transfemoral transcatheter aortic valve implantation. A total of 185 patients undergoing transfemoral transcatheter aortic valve implantation with either dual Per-close ProGlide (n = 139) or a combination of dual Perclose ProGlide and Angio-Seal (n = 46) were retrospectively analyzed. The baseline, procedural characteristics, and all outcomes (defined according to Valve Academic Research Consortium-2 criteria) were compared. Results: No significant differences were seen between the dual Perclose ProGlide vs dual Perclose ProGlide+Angio-Seal groups with regard to the in-hospital Valve Academic Research Consortium-2 primary end points of major vascular complications (n = 13 [9.4%] vs n = 2 [4.3%]; P =.36), minor vascular complications (n = 13 [9.4%] vs n = 8 [14.7%]; P =.14), major bleeding (n = 16 [11.5%] vs n = 2 [4.3%]; P =.25), and minor bleeding (n = 9 [6.5%] vs n = 5 [10.9%]; P =.34), with higher rates of hematoma in the dual Perclose ProGlide+Angio-Seal group (n = 4 [2.9%] vs n = 5 [10.9%]; P =.044). Conclusion: Finding from the current study suggest that adjunctive Angio-Seal deployment may be feasible and safe, especially in patients with incomplete hemostasis following dual Perclose ProGlide use, and can be an optimal “bailout” procedure. (Tex Heart Inst J. 2022;49(6):e217684).
Keywords: Peripheral Artery Diseases; Hemostasis; Vascular Access Device